Isotopic and elemental ratios to assess the relationship between heuweltjies and saline groundwater in the Northern Cape of South Africa. - Van Gend, Jani (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.